PROPAGATION OF MANGO SEEDLINGS OF THE CULTIVAR “TOMMY” BY GRAFTS IRRADIATED (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Due to difficulties of vegetative propagating of any pants, many tests were performed with ionizing radiation aiming the modification of the characteristics of the plants for obtaining of the improved genotypes and of smaller size. Rootstock “Espada” cultivar, were used to obtain mango seedlings of “Tommy” cultivar. The cuttings were irradiated with different doses of gamma radiation: 0 (control), 2.5, 5.0, 7.5 and 10.0 Gy, in a source of Cobalt-60 type Gammacell-220, installed in the Center for Nuclear Energy in Agriculture, CENA-USP. After irradiation, was performed the grafting type cleft graft. Was made the first evaluation of height of the plants from the budding grafting after 24 months. Data were subjected by statistic program (SAS) and the means were compared by Tukey test (p